Skill-biased technological change, international trade and the wage structure - Arnd Kölling; Thorsten Schank (Friedrich-Alexander-Universität Erlangen-Nürnberg, Lehrstuhl für Arbeitsmarkt- und Regionalpolitik, 2002)
During the last two decades, the labour demand structure in Germany has experienced a decrease in the demand for the low skilled. Possible explanations for this trend are investigated in this study for West Germany (1994- 1997) using a unique linked employer-employee panel data set for Germany. Estimation results of the conditional labour demand for three different skill types indicate that the major part of the skill structure is determined by wages, while we have found only minor impacts of a skill-biased technological change and of international trade. – – In den letzten beiden Jahrzehnten hat sich die Beschäftigtenstruktur in Deutschland zuungunsten der Un- und Angelernten entwickelt. Mögliche Ursachen für diesen Trend werden in der vorliegenden Studie auf der Basis eines neuen, aus Individual- und Betriebsdaten zusammengefügten Datensatzes, für West-Deutschland (1994-1997) untersucht. Schätzungen der bedingten Arbeitsnachfrage für drei verschiedene Qualifikationsgruppen zeigen, dass der größte Teil der Beschäftigtenstruktur von den Löhnen bestimmt wird, während nur geringe Einflüsse des technologischen Wandels und des internationalen Handels identifiziert werden.
Keywords: J23; J31; O33; F16; 330; labour demand; substitution; skill-biased technological change; labour hoarding; international trade; linked employer-employee data; Arbeitsnachfrage; Qualifikation; Arbeitsangebot; Lohnstruktur; Technischer Fortschritt; Außenwirtschaft; Schätzung; Deutschland; Matching